PENGARUH LIKUIDITAS, PROFITABILITAS, DAN LEVERAGE TERHADAP RETURN SAHAM - Puspitasari, Yeni; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine 1) the influence of current ratio to the stock return; 2) the influence of net profit margin to the stock return; 3) the influence of return on equity to the stock return; 4) the influence of debt to equity ratio to return stock of pharmaceutical companieswhich are listed in the IDXin 2009-2014 periods. This research is categorized as causal correlational research. The population is the pharmaceutical sector companies which are listed in Indonesia Stock Exchange in 2009-2014 periods. 9 sample companies have been obtained by using purposive sampling and determined criteria, so 54 samples have been applied in this research. The data analysis has been carried out by using classic assumption test, multiple regression, and hypothesis test. The results of the research show that: 1) current ratio does not have any influence to the stock return because this ratio only shows the capability of the company to cover their current liability by using cash so this ratio is not calculated by the investors; 2) Net profit margin has an influence to the stock return because when the net profit margin is getting high, the stock return will be high as well and vice versa; 3) return on equity has an influence to the stock return because when the return on equity is getting high, the stock return will be high as well and vice versa; 4) debt to equity ratio does not have any influence to the stock return because the investors more notice the capability of the company to generate high profit than the debt level.Keywords: Current ratio, net profit margin, return on equity, debt to equity ratio, stock return